Perencanaan Proses Pembelajaran Pendidikan Agama Islam di Sekolah Tahfizh Plus Khoiru Ummah Bogor - Sadiah, Sadiah; Mujahidin, H.E (Madania: Jurnal Ilmu-Ilmu Keislaman, 2023)
The aim of this research is to describe and analyze the planning of the Islamic Religious Education learning process at Tahfidz Plus Khoiru Ummah School, Bogor. The research approach uses qualitative with a case study approach. Data sources are school principals, deputy principals and subject teachers. The data collection technique is observation, interviews and documentation. Data analysis and processing is carried out by means of data reduction, presentation and drawing conclusions. The data obtained was validated by triangulating the same data revealed from various sources. The results of the research show that the planning of the Islamic Religious Education learning process at Tahfidz Plus Khoiru Ummah School in Bogor includes: (1) Teachers create learning tools, (2) Teachers set learning objectives, (3) Teachers select and develop teaching materials, (4) Teachers selecting appropriate teaching media, (5) teachers selecting and utilizing learning resources and, (6) teachers conducting learning assessments. This is in accordance with the implementation of the Islamic faith-based Tahfidz Plus Khoiru Ummah Bogor School curriculum.